Keystone flaps in coloured skin: Flap technology for the masses? - Satish P Bhat (Indian Journal of Plastic Surgery)
Introduction: Viscoelastic properties of skin in coloured ethnic groups are less favourable compared to Caucasians for executing Keystone flaps. Keystone flaps have so far been evaluated and reported only in Caucasians. The potential of Keystone flaps in a coloured ethnic group is yet unknown. Aim: This article reviews the experience to reconstruct skin defects presenting in a coloured ethnic group, by using Keystone flaps, with a review of existing literature. Design: Uncontrolled case series. Materials and Methods: This retrospective review involves 55 consecutive Keystone flaps used from 2009 to 2012, for skin defects in various locations. Patient demographic data, medical history, co-morbidity, surgical indication, defect features, complications, and clinical outcomes are evaluated and presented. Results: In this population group with Fitzpatrick type 4 and 5 skin, the average patient age was 35.73. Though 60% of flaps (33/55) in the series involved specific risk factors, only two flaps failed. Though seven flaps had complications, sound healing was achieved by suitable intervention giving a success rate of 96.36%. Skin grafts were needed in only four cases. Conclusions: Keystone flaps achieve primary wound healing for a wide spectrum of defects with an acceptable success rate in a coloured skin population with unfavorable biophysical properties. By avoiding conventional local flaps and at times even microsurgical flaps, good aesthetic outcome is achieved without additional skin grafts or extensive operative time. All advantages seen in previous studies were verified. These benefits can be most appreciated in coloured populations, with limited resources and higher proportion of younger patients and unfavorable defects.